INTERNATIONAL BUSINESS AND STRATEGIC EXPANSION: A BRAZILIAN LEADING BILLION-DOLLAR VENTURES ACROSS THE AMERICAS (International Seven Journal of Multidisciplinary, 2022)
This article explores the internationalization strategies and leadership of Joe Douglas, a Brazilian entrepreneur at the forefront of billion-dollar business ventures expanding across the United States, Brazil, and Latin America. It examines how Douglas integrates cultural intelligence, dynamic capabilities, and institutional entrepreneurship to foster transnational ecosystems for innovation and investment. The study highlights the role of the DX Business Center in Florida as a strategic hub for cross-border entrepreneurial collaboration and economic development. Grounded in academic frameworks such as born global theory and dynamic capabilities, the article connects real-world business leadership to emerging trends in global entrepreneurship, particularly among Latin American enterprises. The case of Joe Douglas exemplifies how private-sector leadership can bridge institutional voids, catalyze regional integration, and redefine international business strategy in a rapidly evolving global economy.